Community corrections in South Africa - Fitz, Lincoln G. (The Routledge handbook on global community corrections, 2024)
The community corrections system in South Africa is tasked with the supervision and management of over 60,000 people convicted of criminal offenses who are placed on community-based alternatives to incarceration. The agency provides comprehensive supervision services and situates its approach in a needs-based, restorative, and rehabilitative framework, while also emphasizing the community's role in supporting and promoting reintegration. This chapter provides an overview of the Community Correctors sub-area of the Department of Correctional Services in South Africa, including describing the supervised populations, practices and policies, key legislation, and other information related to understanding how South Africa is increasing alternatives to incarceration and endeavors to create a community-driven and evidence-based system of Community Corrections.